2016
DOI: 10.1002/chem.201600859
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bond and Supramolecular‐Contact Mediated Fluorescence Enhancement of Electrochromic Azomethines

Abstract: An electronic push-pull fluorophore consisting of an intrinsically fluorescent central fluorene capped with two diaminophenyl groups was prepared. An aminothiophene was conjugated to the two flanking diphenylamines through a fluorescent quenching azomethine bond. X-ray crystallographic analysis confirmed that the fluorophore formed multiple intermolecular supramolecular bonds. It formed two hydrogen bonds involving a terminal amine, resulting in an antiparallel supramolecular dimer. Hydrogen bonding was also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 70 publications
4
19
0
Order By: Relevance
“…A linear correlation between the chemical shift to higher frequencies together with increasing concentrations was noticed. This behavior confirms the presence of concentration-induced hydrogen bonding [18].…”
Section: Hydrogen Bond Formation: Theoretical and Experimental Approasupporting
confidence: 78%
See 4 more Smart Citations
“…A linear correlation between the chemical shift to higher frequencies together with increasing concentrations was noticed. This behavior confirms the presence of concentration-induced hydrogen bonding [18].…”
Section: Hydrogen Bond Formation: Theoretical and Experimental Approasupporting
confidence: 78%
“…8) except for AzTh-2b, and AzTh-4b, which were non-emissive due to quenching effect typically observed in solid state [11]. As it was shown, amine groups in unsymmetrical imines can create hydrogen bonds, which should improve the luminescence [18]. It was found that all unsymmetrical imines in film exhibited luminescence, probably due to H-bonds formation.…”
Section: Geometric Structure and Frontier Molecular Orbitalsmentioning
confidence: 86%
See 3 more Smart Citations